Replacing the growing media to reduce the seedling weight of citrus (Citrus nobilis var. Microcarpa) and its effects on seedling growth. Issue 1 (May 2021) - Umar, A; Marzuki, S U; Warman, R
Abstract: Seedling translocation of citrus plant is labor-intensive and expensive. It is heavy due to the large amount of soil that is needed to growth the seedlings. This research aimed to overcome the difficulties by reducing or replacing the growth media of the seedling and examined its effects on the seedling growth. The trial was conducted in Monterado Experimental Farm, Bengkayang Regency, West Kalimantan. There were two factors in the experiment, i.e. the type of growing media and biological agent. The type of growing media factor consisted of two levels, soil and cocopeat, while the biological agent factor consisted of three levels, Trichoderma, Bioboost©, and control. The sample seedlings were selected using simple random sampling method. The results showed the survival rate was 100% for all treatments. The use of soil reduced 59.25% of the initial seedling weight, while cocopeat reduced the weigh up to 77.84%. There were no significant differences in the number of leaves, leaf width, number of shoots and shoot lengths caused by different growing media and the application of the biological agents.